Unselfing : global French literature at the limits of consciousness - Hulstyn, Michaela (University of Toronto romance series., 2022)
"Altered states of consciousness--including experiences of deprivation, pain, hallucination, fear, desire, alienation, and spiritual transcendence--can transform the ordinary experience of selfhood. Unselfing explores the nature of disruptive self-experiences and the different shapes they have taken in literary writing. The book focuses on the tension between rival conceptions of unselfing as either a form of productive self-transcendence or a form of alienating self-loss. Michaela Hulstyn explores the shapes and meanings of unselfing through the framework of the global French literary world, encompassing texts by modernist figures in France and Belgium alongside writers from Algeria, Rwanda, and Morocco. Together, these diverse texts prompt a re-evaluation of the consequences of the loss or the transcendence of the self. Through a series of close readings, Hulstyn offers a new account of the ethical questions raised by altered states and shows how philosophies of empathy can be tested against and often challenged by literary works. Drawing on cognitive science and phenomenology, Unselfing provides a new methodology for approaching texts that give shape to the fringes of conscious experience."--